Q. 14.1( 15 Votes )

<a name="MTBlankE

Answer :




= (x2 – x + 1) × (x + 1) – (x + 1) × (x – 1)


= x (x2 – x + 1) + 1 (x2 – x + 1) – (x2 – 1)


[ (a – b)(a + b) = (a2 – b2)]


= x3 – x2 + x + x2 – x + 1 – x2 + 1


= x3 – x2 + 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers